Creativity in public relations - Green, Andy, ....- (London : Kogan Page, 2007)
1. A definition of 'creativity' 2. Creativity: some myths debunked 3. How you think in 'boxes' 4. The creative process 5. Green Light thinking: creative techniques 6. Green Light thinking: brainstorming 7. Creativity - the consultation tool 8. Red Light thinking: the evaluation of ideas 9. Creativity is not just for photocalls 10. Obstacles to creativity 11. You are never more than 12 feet from an opportunity 12. The 'creative diamond' 13. The creative individual 14. Creating a creative culture 15. The ethics of creativity: lies, damned lies 16. The future of creativity 17. Award ceremony 18. Interested in finding out more?
Keywords: Creatief denken; Creativiteit; Public relations